Transforming growth factor‐β in liver cancer stem cells and regeneration. Issue 6 (21st July 2017) - Rao, Shuyun; Zaidi, Sobia; Banerjee, Jaideep; Jogunoori, Wilma; Sebastian, Raul; Mishra, Bibhuti; Nguyen, Bao‐Ngoc; Wu, Ray‐Chang; White, Jon; Deng, Chuxia; Amdur, Richard; Li, Shulin; et al.
Abstract : Cancer stem cells have established mechanisms that contribute to tumor heterogeneity as well as resistance to therapy. Over 40% of hepatocellular carcinomas (HCCs) are considered to be clonal and arise from a stem‐like/cancer stem cell. Moreover, HCC is the second leading cause of cancer death worldwide, and an improved understanding of cancer stem cells and targeting these in this cancer are urgently needed. Multiple studies have revealed etiological patterns and multiple genes/pathways signifying initiation and progression of HCC; however, unlike the transforming growth factor β (TGF‐β) pathway, loss of p53 and/or activation of β‐catenin do not spontaneously drive HCC in animal models. Despite many advances in cancer genetics that include identifying the dominant role of TGF‐β signaling in gastrointestinal cancers, we have not reached an integrated view of genetic mutations, copy number changes, driver pathways, and animal models that support effective targeted therapies for these common and lethal cancers. Moreover, pathways involved in stem cell transformation into gastrointestinal cancers remain largely undefined. Identifying the key mechanisms and developing models that reflect the human disease can lead to effective new treatment strategies. In this review, we dissect the evidence obtained from mouse and human liver regeneration, and mouse genetics, to provide insight into the role of TGF‐β in regulating the cancer stem cell niche. ( Hepatology Communications 2017;1:477–493)